2018
DOI: 10.1038/s41433-018-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography characteristics in diabetic patients without clinical diabetic retinopathy

Abstract: Purpose The purpose of this study is to measure optical coherence tomography angiography (OCTA)-defined retinal vascular and choriocapillaris parameters in diabetic patients without clinically evident diabetic retinopathy. Methods Retrospective case series of eyes in patients with a documented history of either type 1 or type 2 diabetes mellitus without any clinical signs of diabetic retinopathy seen at the Vanderbilt Eye Institute. All eyes underwent dilated funduscopic examination along with OCTA. OCTA analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 8 publications
0
51
0
2
Order By: Relevance
“…With the advent of widefield OCTA and flow overlay, one can differentiate between NVE and IRMA, both of which signify an advanced stage of DR. 17,83 OCTA can identify microaneurysms, IRMAs, capillary non-perfusion area, and neovascularization even before they are appreciated clinically or on fundus photography. 84 Thompson and colleagues 85 detected microaneurysms on OCTA even before they were seen on dilated clinical examination. Although FFA has higher sensitivity than OCTA on detecting microaneurysms, studies have shown that OCTA can even detect microaneurysms, which are not picked up on FFA.…”
Section: Fazmentioning
confidence: 99%
“…With the advent of widefield OCTA and flow overlay, one can differentiate between NVE and IRMA, both of which signify an advanced stage of DR. 17,83 OCTA can identify microaneurysms, IRMAs, capillary non-perfusion area, and neovascularization even before they are appreciated clinically or on fundus photography. 84 Thompson and colleagues 85 detected microaneurysms on OCTA even before they were seen on dilated clinical examination. Although FFA has higher sensitivity than OCTA on detecting microaneurysms, studies have shown that OCTA can even detect microaneurysms, which are not picked up on FFA.…”
Section: Fazmentioning
confidence: 99%
“…Previous studies have found decreased retinal thickness in diabetes with minimal or no DR compared with retinal thickness in non-diabetic individuals. 15,31,32 In contrast, other researchers have observed a tendency towards increased retinal thicknesses in individuals with advanced DR. 33…”
Section: Discussionmentioning
confidence: 83%
“…10 OCTA allows visualization of multiple retinal layers with high resolution; thus, it is more sensitive than FA in detecting subtle vascular distortions correlated with early eye conditions. [11][12][13] The recent development of quantitative OCTA offers a unique opportunity to utilize computer-aided disease detection and artificial intelligence (AI) classification of eye conditions. Quantitative OCTA analysis has been explored for objective assessment of, for example, DR, [14][15][16][17] age-related macular degeneration (AMD), 18,19 vein occlusion, [20][21][22][23] and sickle cell retinopathy (SCR).…”
Section: Introductionmentioning
confidence: 99%
“… 10 OCTA allows visualization of multiple retinal layers with high resolution; thus, it is more sensitive than FA in detecting subtle vascular distortions correlated with early eye conditions. 11 13 …”
Section: Introductionmentioning
confidence: 99%